Menyelamatkan planet bumi : Bagaimana membentuk sebuah ekonomi ... / Lester R. Brown - Brown, Lester R.; Flavin, Christopher;Pastel, Sandra;Hermoyo (Yayasan Obor Indonesia, 1994)
xviii, 231 hlm. : ilus. ; 21 cm.